2011
DOI: 10.1111/j.1651-2227.2011.02170.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity phototherapy for the treatment of severe nonhaemolytic neonatal hyperbilirubinemia

Abstract: High-intensity phototherapy significantly reduces TSB in nonhaemolytic severe hyperbilirubinaemia and decreases the need for exchange transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
2
8
0
1
Order By: Relevance
“…The decrease in TSB in our study was in consistent with Edris AA et al, [20] study who revealed that bilisphere decreased the need for exchange transfusion and shortened the duration of phototherapy. These results are also in agreement with previous studies that show that serum bilirubin levels in neonates may be controlled more effectively with bilisphere (high intensity phototherapy) than with conventional phototherapy [21].…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in TSB in our study was in consistent with Edris AA et al, [20] study who revealed that bilisphere decreased the need for exchange transfusion and shortened the duration of phototherapy. These results are also in agreement with previous studies that show that serum bilirubin levels in neonates may be controlled more effectively with bilisphere (high intensity phototherapy) than with conventional phototherapy [21].…”
Section: Discussionsupporting
confidence: 93%
“…The high correlation also suggests that the percentage of reduction in bilirubin levels during the 6-12-hour interval is closely dependent on the decrease during the 0-6-hour interval. This is also supported by results of the first group in this study as well as those reported by Carvalho et al (14). Moreover, the high correlation suggests a possible relationship between two variables and it is in no way a measure of agreement between them.…”
Section: Relationship Curve Between Percentage Of Reduction and Irrad...supporting
confidence: 91%
“…Similar findings were reported by other authors. Thus, Schindl et al (14) found that the percentage of reduction in bilirubin levels measured at intervals of 2, 4, 6, 12, 18 and 24 hours was 9.4%, 16%, 23%, 40%, 44% and 50%, respectively. If we calculate the percentage of reduction at individual time intervals of 0-2, 2-4 and 4-6 hours, the values come close to each other (9.4%, 7.3% and 8.3%, respectively).…”
Section: Relationship Curve Between Percentage Of Reduction and Irrad...mentioning
confidence: 98%
“…It is highly likely that this improved the rate of phototherapy response in infants with severe hyperbilirubinemia and played a role in the BET rate decline. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%